TEACHER PERCEPTIONS OF THE PROJECT BASED LEARNING IN SPEAKING CLASS - Walhidayah, Walhidayah; Tahir, Muhammad; Munir, Munir; Sunra, La; Aeni, Nur (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study explores teachers’ perceptions of implementing Project-Based Learning (PJBL) in ninth-grade speaking classes. As speaking skills are essential for effective communication and academic success, innovative teaching methods like PJBL are increasingly viewed as strategies to enhance student engagement and learning outcomes. Through qualitative methods, including semi-structured interviews and classroom observations, this research investigates how teachers perceive the effectiveness, challenges, and benefits of using PJBL in speaking instruction. The findings reveal that teachers generally hold both positive and negative perceptions of PJBL. They appreciate its ability to improve student motivation, collaboration, and speaking fluency, while also identifying practical challenges such as time constraints, differing student proficiency levels, and limited teacher training. The study concludes that PJBL holds significant promise for improving students’ speaking skills in junior high schools, yet its success relies on systemic support, sufficient resources, and continuous teacher professional development.